PENAFSIRAN AL-QUR’AN DENGAN FILSAFAT: TELAAH KITAB MAFĀTĪḤ AL-GHAYB FAKHRUDDĪN AL-RĀZĪ - Zunairoh, Yuyun (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Qur?anic exegesis has existed since the life of the Prophet Muhammad. It is divided into two forms, i.e. bi alma?th?r and bi al-ra?y. Tafsir Falsafi is part of tafsir bil ra?y, which is built upon reasoning when interpreting the Qur?an. Some scholars reject this interpretation, but some accept it. Tafsir Falsafi is to interpret the Qur?anby using philosophical approaches. Among the scholars are al-Far?b?, Ibn S?n?, Ikhw?n al-?af?, and Fakhrudd?n al-R?z?. This paper will study Fakhrudd?n al-R?z?, one of the most leading scholars in the subject, by focusing on his great work the Maf?t?? al-Ghayb. This paper will examine a method of interpretation of al-R?z?, which is ta?l?l?.Keywords: Tafsir Falsafi, Maf?t?? al-Ghayb, Fakhrudd?n al-R?z?